Dynamics of incidence of mental and behavior disorders in children of Ukraine: a 25-years’ observation experience. - O. P. Volosovets; Y. K. Bolbot; A. O. Volosovets; L. E. Trachuk; S. P. Kryvopustov; G. V. Beketova; A. Ya. Kuzmenko (Medičnì Perspektivi)
Disorders of the psyche and behavior among children is an urgent problem of modern pediatric science and medical practice. The high prevalence of this pathology may be a result of the unfavorable psychological state of society, aggressive effects of the unfiltered information and negative influence of the environment (including radiatioactive factors) on the mind and body of the child. We have studied a 25-years’ trends in morbidity of mental illneses and behavior disorders among children of Ukraine in order to determine the impact of environmental factors (in particular - radioactivity after Chernobyl disaster in 1986) on their development. We have performed an analysis of the incidence and prevalence of psychiatric and behavioral disorders (PBD) among  children from different regions of Ukraine, including radioactive regions, contaminated after Chernobyl disaster. We used methods of statistical evaluation and epidemiological analysis of statistical data about the mental health of children of the country, aquired from the Ministry of Health of Ukraine. Over the past 25 years, we have observed trend of  reducing the incidence of PBD among children of Ukraine to 3.77 cases per 1,000 children (p<0.01) with prevalence of this pathology among children from large industrial and agricultural regions of the country. We have connected this trend with significant toxic influence of environmental factors on the child's organism. The incidence of PBD in the last 25 years among children from the regions of the country contaminated by the Chernobyl accident in 1986  (especially in Chernihiv and Zhytomyr regions) has exceeded the national incidence rates of PBD and its incidence among children from regions without territories of radiological control. In early 1990s the incidence of mental and behavioral disorders was high among children affected by Chornobyl accident. But over the last 25 years the incidence of PBD has become lower and now its level is even lower than among children who permanently lived in areas contaminated by radiation after the Chernobyl accident and the national incidence rate of PBD among children. The results of our 25-years’ follow-up of PBD morbidity among Ukrainian children have shown that children with prolonged exposure to ecotoxic factors, including radiation, have higher levels of prevalence and incidence of mental and behavioral disorders compared with other children. All this testify that there is a need of a proper correction programs and special attention to this cohort of children.